Elevated Triglycerides Levels in Two Infants With Hypoxic‐ischemic Encephalopathy Undergoing Therapeutic Hypothermia and Receiving Parenteral Nutrition. (26th July 2013) - Ting, Joseph Y.; Manhas, Deepak; Innis, Sheila M.; Albersheim, Susan
Abstract : Therapeutic hypothermia has been widely applied to improve the survival/neurodevelopmental outcomes among infants with moderate‐to‐severe hypoxic ischemic encephalopathy (HIE). Due to their critical condition and concerns over feeding tolerance, it is not uncommon to withhold enteral feeds and provide parenteral nutrition (PN) during hypothermia and early rewarming. Here we report 2 infants with HIE undergoing therapeutic hypothermia, and receiving PN, who exhibited early elevated triglyceride levels. Hypertriglyceridemia can be associated with neurologic complications, ranging from altered mental status, or irritability to seizures. Given the possible altered lipid metabolism under hypothermic conditions, we advocate close monitoring of lipid tolerance and conducting further prospective trials to elucidate lipid metabolism in these infants.